2011
DOI: 10.1186/1476-511x-10-229
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophages exhibit higher sensitivity to oxLDL-induced lipotoxicity than other monocyte/macrophage subtypes

Abstract: BackgroundIn obesity, phenotypic switches occur in macrophage populations such that the predominantly M2-polarised anti-inflammatory state seen in lean individuals changes to a predominantly M1-polarised pro-inflammatory state in those who are obese. However, the mechanisms by which these phenotypic shifts occur have not yet been fully elucidated.ResultsThe effects of oxLDL (1-40 μg/ml; 24 h) on several parameters relevant to the Unfolded Protein Response (UPR)-mediated lipotoxic effects of oxLDL (disruption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…They determined that M2 macrophages are more sensitive to the lipotoxicity induced by Ox-LDLs, as compared to M0 macrophages and to monocytes. Anew, in the latter study, only copper-oxidized LDLs were evaluated and only M0 and M2 macrophages were taken into account [ 59 ]. van Tits et al (2011) have shown that Ox-LDLs enhance proinflammatory responses stimulated by LPS in human M2 macrophages, which is in agreement with our data showing proinflammatory effects of Ox-LDLs.…”
Section: Discussionmentioning
confidence: 99%
“…They determined that M2 macrophages are more sensitive to the lipotoxicity induced by Ox-LDLs, as compared to M0 macrophages and to monocytes. Anew, in the latter study, only copper-oxidized LDLs were evaluated and only M0 and M2 macrophages were taken into account [ 59 ]. van Tits et al (2011) have shown that Ox-LDLs enhance proinflammatory responses stimulated by LPS in human M2 macrophages, which is in agreement with our data showing proinflammatory effects of Ox-LDLs.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were obtained using a previously described method [ 22 , 23 ]. Briefly, we mixed the human peripheral blood sample with an equal volume of room temperature PBS, pelleted the leukocyte/RBC fraction by centrifuging the cells 15 min at 200 × g , at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of UPR function in macrophages is strongly correlated with disease, including fibrosis [110], obesity-induced inflammatory disease [111,112], tuberculosis [113], and fatty liver disease [114]. These studies associate macrophage-induced inflammation via UPR signaling in these diseases, such that inhibition of UPR signaling abrogated or ablated disease.…”
Section: Upr Signaling In Macrophagesmentioning
confidence: 99%